New Testament: New King James Version - International Bible Society (International Bible Society, 1982)
New King James Version: New Testament is a bible printed by the International Bible Society to faithfully translate and reach out with God's word so that people around the world may become disciples of Jesus Christ and members of his body.
Keywords: Religion / Bible-New Testament-King James Version